Genotype-Guided Thiopurine Dosing Does not Lead to Additional Costs in Patients With Inflammatory Bowel Disease. (30th January 2019) - Sluiter, Reinier L; van Marrewijk, Corine; de Jong, Dirk; Scheffer, Hans; Guchelaar, Henk-Jan; Derijks, Luc; Wong, Dennis R; Hooymans, Piet; Vermeulen, Sita H; Verbeek, André L M; Franke, Barbara; van der Wilt, Gert Jan; et al.
Abstract: Background and Aims: Decreased thiopurine S -methyltransferase [TPMT] enzyme activity increases the risk of haematological adverse drug reactions [ADRs] in patients treated with thiopurines. Clinical studies have shown that in patients with inflammatory bowel disease [IBD], pharmacogenetic TPMT -guided thiopurine treatment reduces this risk of ADRs. The aim of this study was to investigate whether this intervention impacts on healthcare costs and/or quality of life. Methods: An a priori defined cost-effectiveness analysis was conducted in the Thiopurine response Optimization by Pharmacogenetic testing in Inflammatory bowel disease Clinics [TOPIC] trial, a randomized controlled trial performed in 30 Dutch hospitals. Patients diagnosed with IBD [age ≥18 years] were randomly assigned to the intervention [i.e. pre-treatment genotyping] or control group. Total costs in terms of volumes of care, and effects in quality-adjusted life years [QALYs], based on EuroQol-5D3L utility scores, were measured for 20 weeks. Mean incremental cost savings and QALYs with confidence intervals were calculated using non-parametric bootstrapping with 1000 replications. Results: The intervention group consisted of 381 patients and the control group 347 patients. The mean incremental cost savings were €52 per patient [95% percentiles −682, 569]. Mean incremental QALYs were 0.001 [95% percentiles −0.009, 0.010]. Sensitivity analysis showed that the results were robust for potential change in costs of screening, costs of biologicals and costs associated with productivity loss. Conclusions: Genotype-guided thiopurine treatment in IBD patients reduced the risk of ADRs among patients carrying a TPMT variant, without increasing overall healthcare costs and resulting in comparable quality of life, as compared to standard treatment.